2022
DOI: 10.1037/stl0000216
|View full text |Cite
|
Sign up to set email alerts
|

Learning from mistakes: Teaching students about errata, corrigenda, and nonretraction corrections to the research literature.

Abstract: Publication guidelines indicate that when substantive errors in research are noted after the publication of a research report, a correction (also known as an erratum or corrigendum) should be issued. Although such corrections are published with some regularity in psychology and in other scientific fields, the issue of corrections to the scientific literature is seldom addressed in the kinds of research methods textbooks often used in undergraduate psychology courses. This article briefly reviews the existing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Our review demonstrated that there is a plethora of peer-reviewed articles in this area. Haas & Rouse [ 91 ], for example, recommend that students be introduced to the concept of correction in the scientific record and taught how to identify and interpret correction notices during a literature search. One of the key requirements of a reliable scientific record is that publishers issue corrections whenever substantive errors in published research are identified.…”
Section: Open and Reproducible Scholarship And Students' Scientific L...mentioning
confidence: 99%
“…Our review demonstrated that there is a plethora of peer-reviewed articles in this area. Haas & Rouse [ 91 ], for example, recommend that students be introduced to the concept of correction in the scientific record and taught how to identify and interpret correction notices during a literature search. One of the key requirements of a reliable scientific record is that publishers issue corrections whenever substantive errors in published research are identified.…”
Section: Open and Reproducible Scholarship And Students' Scientific L...mentioning
confidence: 99%
“…Our review demonstrated that there is a plethora of peer-reviewed articles in this area. Haas and Rouse (2022) recommend that students be introduced to the concept of correction in the scientific record, associated terminology, and taught how to identify and interpret correction notices, when encountered during a literature search. One of the key requirements of a reliable scientific record is that publishers issue corrections whenever substantive errors in published research are identified.…”
Section: Students' Consumption Of Sciencementioning
confidence: 99%
“…There is also a plethora of recent evidence that supports the need for incorporating this approach into undergraduate and postgraduate training (e.g., Button, 2018; FORRT, 2019; Pownall, 2020). This has led to discussions related to teaching undergraduate students about the factors that have contributed to the “replication crisis,” which is the growing concern about the lack of successful replications of published research (Chopik et al, 2018; Haas & Rouse, 2020). Similarly, there have been efforts to address QRPs in student research (Sacco & Brown, 2019; Strand & Brown, 2019; Wagge et al, 2019), and considerations of how to integrate this approach across teaching curricula (Frank & Saxe, 2012; Frankowski, 2021; Hanna et al, 2021; Sarafoglou et al, 2020).…”
Section: The Need For Open Educational Resourcesmentioning
confidence: 99%